A combined rapid test for detecting arbovirus antibodies in blood specimens - Venter, Phydelia Christine (Bloemfontein: Central University of Technology, Free State, 1994)
Arboviruses (arthropod-borne viruses) are viruses that are maintained in nature through transmission between susceptible vertebrate hosts by haematophagous arthropods. These viruses multiply and produce viraemia in the vertebrates, replicate In the tissue of arthropods, and are then passed on to new vertebrates by the bites of these arthropods (Simpson, 1984). There are 504 arboviruses registered in the International Catalogue of Arboviruses (Labuda, 1991) of which approximately 100 are capable of infecting man. The majority of arboviruses have been serologically classified in the families; Togaviridae, Flaviviridae, Reoviridae, Bunyaviridae, and Rhabdoviridae. Mosquitoes are the most important arbovirus vectors, followed by ticks. Phlebotomines, Culicoides species and Cimex species are also involved in the transmission of some arboviruses (Simpson, 1984). Studies have shown that Sindbis (SIN), West Nile (WN), Rift Valley fever (RVF) and Wesselsbron (WSL) viruses are the most prevalent arboviruses in the Orange Free State (Mcintosh, 1980) and with generalised clinical symptoms such as fever, headache, general malaise, muscle or jOint pains and a macular or maculopapular rash (Lennette & Schmidt, 1979) a conclusive diagnosis for arbovirus infections can only be made by the laboratory. Standard tests for identifying viruses or detecting viral antibodies are often time consuming, expensive and necessitate sophistication. No commercial diagnostic kits are available for detecting antibodies to certain arbovlruses, therefore, it was necessary to develop a simple, cost-effective test for screening and determining specific antibodies of the immunoglobulin G (lgG) and Immunoglobulin M (lgM) class against RVF, SIN, WN and WSL viruses. In the conventional enzyme-linked immunosorbent assays (ELISA) for detecting viral antigens and antibodies, polystyrene or other materials (which have a rather low binding capacity for proteins) are generally used as the solid phase. On the other hand, the superior binding capacity of nitrocellulose (NC) for the adsorption of proteins from a polyacrylamide gel following electrophoresis by the Western blot technique, has been demonstrated and implicated the advantageous use of NC instead of polystyrene as the solid phase (Towbin et al. 1979). The aim of this study was to develop a dot-ELISA by using a NC membrane as solid phase on which to spot antigens for later visualisation of antigen-antibody complexes of RVF, SIN, WN and WSL with enzyme-conjugated anti-human immunoglobulins of the IgG, as well as the IgM class, using a substrate which gives an insoluble colour reaction.
Thesis
Keywords: Blood - Analysis; Blood - Examination; Arbovirus infections - South Africa - Diagnosis; Arbovirus infections